PENGARUH SOLUTION ANNEALING DAN AGING PADA KAWAT PADUAN SHAPE MEMORY Ni-Ti DAN Ni-Ti-Cu[The Influence of Solution Annealing and Aging on Ni-Ti and Ni-Ti-Cu Shape Memory Alloy Wire] - Mabruri, Efendi; Sriyono, Bambang; Adjiantoro, Bintang; Adnyana, D N (Jurnal Metalurgi, 2012)
THE INFLUENCE OF SOLUTION ANNEALING AND AGING ON Ni-Ti AND Ni-Ti-Cu SHAPE MEMORY ALLOY WIRE. The influence of solution annealing and aging on NiTi and NiTiCu shape memory alloy has been investigated. The alloys in wire form were fabricated through vacum arc melting, hot pressing, hot rolling, wire drawing and finally heat treating of solution annealing dan aging). The alloy wire was characterized by thermal analysis (DSC), XRD and bending-heating test to measure the shape memory effect (SME). The experimental results showed that the Ni-Ti-Cu wire (Ni-49.7Ti-9.2Cu) exhibited one-way SME higher than that of the Ni-Ti wire (Ni-48.8Ti) in both conditions of solution annealed and aged. The two-way SME exhibited by solution annealed NiTi wire was larger than that exhibited by aged NiTi wire. With respect to NiTiCu wire, the alloy conditions (solution annealed and aged) relatively had no effect on the two-way SME of the alloy. Finally, it was found that the effect of Cu on two-way SME was larger in the aged Ni-Ti alloy than in solution annealed Ni-Ti alloy.